INTERNET BANKING IN THE CONTEXT OF DIGITALIZATION: ADVANTAGES AND DISADVANTAGES (World Bulletin of Management and Law, 2023)
The article describes the essence of Internet banking in the digital economy as well as its advantages and disadvantages
Keywords: Digital economy; Internet banking; banking services